Physical Characterization of Cu2basns4 Thin Films Deposited At DifferentConcentrations of Sulfur Ions by Chemical Spray Pyrolysis Method - Hamsa J. Ata; Ali, Nabeel; Ahmed, Asaad (ASJ - Academic Science Journal, 2025)
In this work, Cu2BaSnS4 thin films were deposited on soda-lime glass by the chemical spray pyrolysis technique (CSP) at different concentrations of thiourea, with a thickness of about 350 ±10 nm measured by the gravimetric method. The thin films structural and morphological properties were investigated using X-ray diffraction (XRD), Raman spectroscopy, Field Emission Scanning Electron Microscopy (FE-SEM), and Atomic Force Microscopy (AFM), as well as optical properties using a UV-Vis spectrophotometer at the wavelength range (300–900) nm. We investigated the electrical properties using the Hall effect. Optical band gap of CBTS thin films increased from (1.757 to 1.923) eV when concentrations of thiourea increased from (0.04 to 0.12) M. The Cu2BaSnS4 (CBTS) films have a high absorption coefficient (α > 104 cm-1), indicating allowed direct electron transmission. XRD measurements of Cu2BaSnS4 (CBTS) films revealed a trigonal crystal structure. The XRD pattern preferred the (104) orientation, which has a high intensity and indicates that crystallization is most likely to occur along this plan. Raman spectroscopy of CBTS thin films revealed a protruding peak at 341 cm-1. The morphological findings and FE-SEM photographs of the thin film surface revealed a variety of structures and forms, one of which resembled cauliflower. Electrical tests revealed the conductivity of (p-type). The calculated electrical conductivity of CBTS thin films was found in the range of 0.053 - 0.184 (Ω.cm)-1. Based on our findings, the Cu2BaSnS4 (CBTS) thin films look to be an excellent choice for an absorber layer in solar cells.